2014
DOI: 10.1007/s00520-014-2440-8
|View full text |Cite
|
Sign up to set email alerts
|

Palliative performance scale and survival among outpatients with advanced cancer

Abstract: Given the ongoing challenge of inaccurate survival estimates, this data suggests what may be of greatest clinical utility is to use specific PPS ratings as triggers for key care discussions among patients with incurable and progressive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
3
20
0
1
Order By: Relevance
“…We also found that the higher Palliative Performance Scale, chemotherapy, and radiotherapy were among the factors strongly correlated with longer survival of the patients, which was consistent with previous reports [4144]. Moreover, the patients that visited the palliative care clinic or had a home visit tended to survive longer, and the patients that needed hospital admission lived a shorter length of time in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the higher Palliative Performance Scale, chemotherapy, and radiotherapy were among the factors strongly correlated with longer survival of the patients, which was consistent with previous reports [4144]. Moreover, the patients that visited the palliative care clinic or had a home visit tended to survive longer, and the patients that needed hospital admission lived a shorter length of time in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We took this approach because follow-ups were not spaced evenly in the original trial design, and data were highly likely to be missing not-at-random due to patient decline and death. Functional status has been used to explore ACL (5) and track symptom burden (13) in palliative care patients; it has also been found to be a significant predictor of survival in these populations (1416). By evaluating ACL based on performance status (AKPS), we maintained our sample size (n=244; 1,210 encounters).…”
Section: Methodsmentioning
confidence: 99%
“…Performance status [22][23][24], dyspnea [25,26], malnutrition [27,28], appetite/weight loss [29], and delirium [30,31] are well-known clinical factors. Recently, novel prognostic factors have been proposed.…”
Section: Prognostic Factorsmentioning
confidence: 99%